Distance to default and probability of defaultdan experimental study - Amir Ahmad Dar; Shahid Qadir (Journal of Global Entrepreneurship Research, 2019)
The distance to default (DD) and the probability of default (PD) are the essential credit risks in the finance world. It provides an estimate of the likelihood that a borrower will be unable to meet its debt obligations. It is crucial to know which parameter effects more on DD and PD so that investor will prevent future risks. Purpose: The purpose of this study is to investigate the effects of four parameters (asset value of firm V, value of debt X, interest rate r and the volatility of asset σ at one period) on DD and PD. Design/methodology/approach: The Black Scholes model is used to estimate the DD and PD. To explore the effects of parameters, the author used Taguchi's L27 orthogonal array, analysis of variance (ANOVA) and analysis of mean (ANOM), and the analysis will carry out using MINITAB software. The effect of parameters will be discussed with the main effect plot and the average response on a response plot showing the best outcomes. Findings: ANOM identified the optimal combination where the DD is a maximum, and the PD is a minimum. The percentage contribution of each input factor on DD and PD was estimated by conducting ANOVA. The above two (DD and PD) exists an inverse relationship. The rank or percentage contribution will vary with change in the data set.
Keywords: 650; Taguchi method; Probability of default; Distance to default; Black Scholes Merton model; ANOM; ANOVA; Orthogonal arrays